Designing a Digital Content Marketing Model with a Customer Engagement Approach in Commercial Banks - Shadzad, Vahidreza; Naami, Abdullah; Kimasi, Masoud; Azad, Naser (Business, Marketing, and Finance Open, 2025)
The main objective of this study is to design and explain a digital content marketing model with a customer engagement approach in commercial banks in Iran. The research method is qualitative and of an exploratory interpretive type, conducted using the grounded theory technique. The reason for using this method was the lack of theoretical and empirical background in the field of the research topic. Data collection for this study was carried out through semi-structured in-depth interviews. The statistical population includes experts, professors, and senior managers in the field of content marketing in the banking industry, from which 13 individuals were purposefully selected for in-depth interviews, and the theorizing process reached theoretical saturation with these thirteen interviews. To design the digital content marketing model with a customer engagement approach, data analysis was performed using coding in the form of open, axial, and selective coding based on the Strauss and Corbin method. The results of this stage of the research identified 11 categories within six groups, including customers' informational needs, customers' functional needs, customers' hedonic needs, digital context and platform, content features, content dissemination and accessibility, prior audience attitudes, customer engagement, brand enhancement, customer loyalty, and increased sales of banking services and products, which were presented within a paradigmatic model. The results of this study can be utilized to enhance digital content marketing with a customer engagement approach in the banking industry.